The Impact of Customer Trust and Perception of Security and Privacy on the Acceptance of Online Banking Services: Structural Equation Modeling Approach - Al-Sharafi, Mohammed A.; Ruzaini, Abdullah Arshah (2016)
The present study aimed to investigate the impact of security and privacy perceptions on bank customers’ trust to accept and adopt online banking services. Specifically, the investigation in the study focused on the factors affecting customers’ trust to accept and use online banking services. In order to achieve this, a survey was administered to a number of 198 participants from Jordan for collecting the data. A Structural Equation Modeling (SEM) approach was utilized for analyzing the respondents’ responses to the survey. The results showed that trust positively affected customers’ behavioral intention to adopt online banking services. Moreover, the customers’ perception, including their perceived usefulness, security and privacy had a significant impact on their trust. However, users’ perceived ease of use failed to predict the customers’ intention to use online banking services. Based on these results, a research model that accurately reflects the factors affecting customers’ trust to accept and use online banking services was developed.